KOMBUCHA: PENDAYAGUNAAN MEKANISME GUT-BRAIN AXIS DALAM PENCEGAHAN DEPRESI - Putu Diah Ananda Putri Atmaja; Abiyyu Didar Haq; Visakha Vidyadevi Wiguna (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2022)
Background: COVID-9 pandemic brings a devastating change on every aspect of everyday life around the world. The change that is happening has been proven to act as a risk factor for many mental illnesses, including depression. Many efforts that has been done mainly focuses on curative aspect of depression and only a small portion of it focuses on the preventive aspect. Methods: This literature review uses a variety of articles sourced from several online publication databases such as National Center for Biotechnology Information (NCBI), Garba Rujukan Digital (GARUDA), and Google Scholar. Discussion: Many clinical studies has proved that there are indeed a connection between gut microbiote witf the nervous system which researchers called Gut-Brain Axis (GBA). Gut microbiote plays a key role in maintaining GBA homeostasis and its relation with one’s mental health. Probiotic consumption is one of many efforts that people do to maintain that homeostasis in order to maintain their mental health. Made of tea, sugar, and Symbitoic Culture of Bacteria and Yeasts (SCOBY) , kombucha is a fermented beverage that has been proven to bring positve impacts on gut microbiote with more than 50 probiotics and beneficial molecules. Conclusion: Utilization of kombucha to maintain GBA has the potential to completes the fight against depression especially in the aspect of prevention